2005
DOI: 10.1021/jm040868q
|View full text |Cite
|
Sign up to set email alerts
|

Novel [2‘,5‘-Bis-O-(tert-butyldimethylsilyl)-β-d-ribofuranosyl]- 3‘-spiro-5‘ ‘-(4‘ ‘-amino-1‘ ‘,2‘ ‘-oxathiole-2‘ ‘,2‘ ‘-dioxide) Derivatives with Anti-HIV-1 and Anti-Human-Cytomegalovirus Activity

Abstract: New [2',5'-bis-O-(tert-butyldimethylsilyl)-beta-d-ribofuranosyl]-3'-spiro-5' '-(4''-amino-1'',2''-oxathiole-2'',2''-dioxide) (TSAO) derivatives substituted at the 4' '-amino group of the spiro moiety with different carbonyl functionalities have been designed and synthesized. Various synthetic procedures, on the scarcely studied reactivity of the 3'-spiroaminooxathioledioxide moiety, have been explored. The compounds were evaluated for their inhibitory effect on both wild-type and TSAO-resistant HIV-1 strains, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…Thus, reaction of 5 a with chlorosulfonyl isocyanate in acetonitrile, followed by treatment with aqueous NaHCO 3 www.chemeurj.org longed reaction time (4 days) at room temperature. When this reaction was carried out in a pressure reaction vessel at 80 8C (general N-acylation conditions used in TSAO nucleoside derivatives), [14] the initially observed N-acyl group of 23 underwent migration to the enaminic C-3 carbon to give the C-acylated product 24 after three hours, in good yield (69 %). It should be noted that N-acylation of the b-aminog-sultone heterocyclic system at room temperature or C-acylation with acyl chlorides has never been observed previously in TSAO nucleoside derivatives.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, reaction of 5 a with chlorosulfonyl isocyanate in acetonitrile, followed by treatment with aqueous NaHCO 3 www.chemeurj.org longed reaction time (4 days) at room temperature. When this reaction was carried out in a pressure reaction vessel at 80 8C (general N-acylation conditions used in TSAO nucleoside derivatives), [14] the initially observed N-acyl group of 23 underwent migration to the enaminic C-3 carbon to give the C-acylated product 24 after three hours, in good yield (69 %). It should be noted that N-acylation of the b-aminog-sultone heterocyclic system at room temperature or C-acylation with acyl chlorides has never been observed previously in TSAO nucleoside derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that N-acylation of the b-aminog-sultone heterocyclic system at room temperature or C-acylation with acyl chlorides has never been observed previously in TSAO nucleoside derivatives. [14] Other carbonyl electrophiles such as aldehydes (previously unexplored in TSAO nucleoside substrates) react with model sultone derivatives 5 a,b exclusively at the C-3 position of the enamine system (Scheme 3). Reaction of 5 b with benzaldehyde in dry THF in the presence of NaH at low temperature (À78 8C) afforded the 3-hydroxyphenylmethyl derivative 25 in low yield.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on the effect of these 3 -TSAO modified compounds on RT dimerization indicate that compound 2 seems to have a higher destabilizing effect dimerization than TSAO-T (unpublished results). In the series of TSAO compounds bearing different carbonyl functionalities at the 4 -position (de Castro et al, 2005), many analogues showed high anti-HIV-1 activity against viral replication, but these 4 -TSAO modified compounds did not show any improvement over the parent TSAO-T as dimerization inhibitors (unpublished results). On the other hand, substitutions at the N-3 position of the thymine base led to compounds endowed with a greater impact on RT dimerization (Bonache et al, 2005) suggesting that interactions with one or more of the dimer interface residues close to the TSAO binding site (Glu138) may help destabilize the RT dimer by disrupting key interface interactions.…”
Section: Hiv-1 Reverse Transcriptase (Dimerization Inhibitors Of Hiv-mentioning
confidence: 96%